UNDERSTANDING THE CHAK PERIOD IN THE HISTORY OF KASHMIR - Dr. Shabir Ahmad Lone; Dr. Nusratul -Islam Itoo; Dr. R. Abida Begum; Dr. B. Sheela (Journal of International Islamic Law, Human Right and Public Policy, 2026)
Inspired by Marcus Garvey’s assertion that a people without knowledge of their past resemble a tree without roots, this study undertakes an exploration of the historical traditions of Kashmir, Jammu, and other regions associated with the Chak dynasty. For the inhabitants of Jammu and Kashmir, engagement with regional history is indispensable, as it forms the foundation of cultural awareness and identity. This work seeks to interpret the legacy of the Chak rulers within the broader historical narrative of Kashmir, often described metaphorically as an “ocean in a pot.” History, rather than ending, continually re-emerges, reflecting both human progress and regression. From prehistory—understood as the period before written records—to documented events, history encompasses the processes of recollection, collection, organization, and interpretation. Kashmir, popularly known as “heaven on earth,” has long attracted political ambition, a sentiment echoed in a Persian couplet attributed to Amir Khusrau. Following the establishment of Muslim rule in 1339 CE, the Chak dynasty governed Kashmir between 1561 and 1586. Despite limited treaty records, their administration largely preserved and strengthened existing institutions. This study examines the enduring political and administrative legacy of the Chak dynasty in Kashmir.